Pregnancy; an opportunity to return to a healthy lifestyle: a qualitative study - Razieh Bagherzadeh; Tayebeh Gharibi; Bahare Safavi; Seyyedeh Zahra Mohammadi; Fatemeh Karami; Sedigheh Keshavarz (BMC, 2021)
Abstract Background The lifestyle of the mother during pregnancy can affectthe health of their baby. Since lifestyle change is a sociocultural act and the motivations associated with lifestyle patterns during pregnancy cannot be explained in quantitative studies, a comprehensive study of the lifestyle during pregnancy and factors influencing its patterns was needed to investigate it from different aspects. Thus, the present study aimed to explore 'mothers' perceptions and experiences about lifestyle patterns during and after pregnancy and the reasons for adopting these lifestyles. Methods The present study, conducted on 20 pregnant or postpartum women living in Bushehr, Iran, has used a conventional content analysis approach. The purposeful sampling method was used with maximum diversity and continued until data saturation. data were collected through face-to-face, in-depth, semi-structured interviews. Informed consent was obtained from all participants, and assuringthe confidentiality of their information. MAXQDA 10 software was used to analyze the data. Results Four main themes were defined after data analysis; "Being a mother as motivation for adopting a new healthy lifestyle"; "Access to information from media and supports from physicians as facilitators of adopting healthy lifestyle"; "Aspects of lifestyle modifications" and "Durability of healthy lifestyles". When women become pregnant, they feel a responsibility tohave a healthy pregnancy. They care about their fetuses more than themselves, which motivated them to look for the best lifestyle. In this way, access information from mass media and recommendations from professionals (physicians, midwives, and other health care providers) were helpful factors to have a healthy lifestyle, leading to modifying physical, mental, and religious aspects of lifestyle. However, despite reminding the advantages of a healthy lifestyle, these changesshift to a pre-pregnancy lifestyle due to the cessation of support and care provided during pregnancy. Conclusion The study results showed that pregnant women should be motivated to modify their lifestyle andadopt healthy lifestyles. Pregnant women seek to modify their lifestyle because of motherhood responsibility and and having a healthy baby. Access to information and supports from various sources promote a mother's inner decision to change, leading to modifying different aspects of life. However, these modifications often shift to the pre-pregnancy lifestyle due to cessation of supports and care, despite reminding the benefits of the lifestyle change. Health care providers should consider supportive measures during pregnancy and postpartum.